Silencing β1,2-xylosyltransferase in Transgenic Tomato Fruits Reveals xylose as Constitutive Component of Ige-Binding Epitopes - Paulus, Kathrin E.; Mahler, Vera; Pabst, Martin; Kogel, Karl-Heinz; Altmann, Friedrich; Sonnewald, Uwe (Frontiers in Plant Science, 2011)
Complex plant N-glycans containing β1,2-xylose and core α1,3-fucose are regarded as the major class of the so-called ‘carbohydrate cross-reactive determinants’ reactive with IgE antibodies in sera of many allergic patients, but their clinical relevance is still under debate. Plant glycosyltransferases, β1,2-xylosyltransferase (XylT) and core α1,3-fucosyltransferase (FucT) are responsible for the transfer of β1,2-linked xylose and core α1,3-linked fucose residues to N-glycans of glycoproteins, respectively. To test the clinical relevance of ß 1,2-xylose containing epitopes, expression of the tomato β1,2-xylosyltransferase was down-regulated by RNA interference (RNAi) in transgenic plants. Fruits harvested from these transgenic plants were analysed for accumulation of XylT mRNA, abundance of ß1,2-xylose epitopes and their allergenic potential. Based on qPCR analysis XylT mRNA levels were reduced up to 10-fold in independent transgenic lines as compared to untransformed control, whereas no xylosylated N-glycans could be revealed by MS analysis. Immunoblotting using anti-xylose-specific IgG antibodies revealed a strong reduction of ß1,2-xylose containing epitopes. Incubating protein extracts from untransformed controls and XylT_RNAi plants with sera from tomato allergic patients showed a patient-specific reduction in IgE binding, indicating a reduced allergenic potential of XylT_RNAi tomato fruits, in vitro. To elucidate the clinical relevance of ß1,2-xylose containing complex N-glycans skin prick tests were performed demonstrating a reduced responsiveness of tomato allergic patients, in vivo. This study provides strong evidence for the clinical relevance of ß1,2-xylose containing epitopes in vivo.